Design Synthesis and Biological Evaluation of Novel N-Nitro Acid Amide Derivatives as Lead Compounds of Herbicide - Xiaojuan Qi; Wenjie Tang; Shan Gao; Min Gao; Changshui Chen; Qingye Zhang (Journal of Chemistry)
A series of N-nitro acid amide derivatives compounds were synthesized based on the active site of target acetohydroxyacid synthase (AHAS, EC: 2.2.1.6) enzyme. All the structures of newly prepared compounds were thoroughly characterized by satisfied IR and 1H NMR spectra. The IC50 values against AHAS enzyme and EC50 values for herbicidal activity against Amaranthus mangostanus L. and Sorghum sudanense of all synthesized target compounds were determined. The compounds II-10, II-21, and II-22 with IC50 values of 7.09 mg/L, 9.07 mg/L, and 9.11 mg/L and the compounds II-8 and II-22 with EC50 values of 9.87 mg/L and 19.88 mg/L against root of Amaranthus mangostanus L. and Sorghum sudanense were illustrated, respectively. Meanwhile, the possible reasons for the lower activity of compounds were analyzed by molecular docking prediction.